Pemberdayaan Pegawai UMKM Keloria Melalui Pelatihan Pembuatan Database Menggunakan Microsoft Access - Vidya Fathimah Vidya; Diana Suksesiwaty Lubis; Tri Utari Ismayuni; Yenny Obsi Satra (Jurnal Pengabdian Masyarakat Eka Prasetya, 2022)
This Community Service will be carried out in 2022 at Keloria UMKM, with the theme "Empowerment of Keloria UMKM Employees Through Database Creation Training Using Microsoft Access". Considering that the development of technology is so fast, knowledge of databases and how to operate it is only natural for Keloria MSMEs to know about it and be able to make it because Keloria MSMEs have grown rapidly, their sales have penetrated abroad. This activity aims, in addition to the interests of lecturers with the Tri Dharma of Higher Education, but also to equip employees with knowledge and techniques for building databases. The software used is Microsoft Access 2007. The benefit that can be taken after this activity is carried out is that apart from the need for lecturers to get functional positions, Keloria UMKM employees can of course build databases related to their work. This activity is only limited to knowledge about databases and how/steps/techniques for making them. For application design as a bridge for input, process and output data, it is necessary to carry out further services in the future.